Tinjauan Hukum Islam Terhadap Tradisi Ngemblok Dalam Prosesi Lamaran : (Studi Kasus Desa Katerban, Tuban) - Nisyatun Nasayatin Nafi’ah; Abdullah Afif (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Sub-District of Senori, Tuban Regency. Generally, the proposal (marriage proposal) that takes place in the village involves men proposing to women, different from that of the village where a woman takes the role as the proposer. This marriage proposal activity conducted by women is called